Bridging research and practice in conservation. Issue 6 (4th June 2021) - Kadykalo, Andrew N.; Buxton, Rachel T.; Morrison, Peter; Anderson, Christine M.; Bickerton, Holly; Francis, Charles M.; Smith, Adam C.; Fahrig, Lenore
Abstract: Calls for biodiversity conservation practice to be more evidence based are growing, and we agree evidence use in conservation practice needs improvement. However, evidence‐based conservation will not be realized without improved access to evidence. In medicine, unlike in conservation, a well‐established and well‐funded layer of intermediary individuals and organizations engage with medical practitioners, synthesize primary research relevant to decision making, and make evidence easily accessible. These intermediaries prepare targeted evidence summaries and distribute them to practitioners faced with time‐sensitive and value‐laden decisions. To be effective, these intermediaries, who we refer to as evidence bridges, should identify research topics based on the priorities of practitioners; synthesize evidence; prepare and distribute easy‐to‐find and easy‐to‐use evidence summaries; and develop and maintain networks of connections with researchers and practitioners. Based on a review of the literature regarding evidence intermediaries in conservation and environmental management, as well as an anonymous questionnaire searching for such organizations, we found few intermediaries that met all these criteria. Few evidence bridges that do exist are unable to reach most conservation practitioners, which include resource managers in government and industry, conservation organizations, and farmers and other private landowners. We argue that the lack of evidence bridges from research to practitioners contributes to evidence complacency and limits the use of evidence in conservation action. Nevertheless, several existing organizations help reduce the gap between evidence and practice and could serve as a foundation for building additional components of evidence bridges in conservation. Although evidence bridges need expertise in research and evidence synthesis, they also require expertise in identifying and communicating with the community of practitioners most in need of clear and concise syntheses of evidence. Article Impact Statement: Evidence‐based conservation will not be realized without improved access to evidence. We call for intermediary evidence bridges. Abstract : Article impact statement : Evidence‐based conservation will not be realized without improved access to evidence. We call for intermediary evidence bridges. Abstract : Vinculación entre la Investigación y la Práctica en la Conservación Resumen: Cada vez existen más peticiones para que las prácticas de conservación de la biodiversidad estén más basadas en evidencias, además de que apoyamos la idea de que el uso de evidencias en la práctica de la conservación necesita mejorar. Sin embargo, la conservación basada en la evidencia no se logrará sin un acceso mejorado a las evidencias. En la medicina, no como en la conservación, un estrato bien establecido y financiado de individuos y organizaciones intermediarias interactúan con los médicos, sintetizan las investigaciones primarias relevantes para la toma de decisiones y hacen que las evidencias sean de fácil acceso. Estos intermediarios preparan resúmenes de evidencias específicas y los distribuyen a los médicos que enfrentan decisiones urgentes y muy valiosas. Para que sean efectivos, estos intermediarios, a quienes nos referimos como puentes de evidencias, deben poder identificar los temas de estudio con base en las prioridades de los practicantes, sintetizar evidencias, preparar y distribuir resúmenes fáciles de encontrar y fáciles de usar, y desarrollar y mantener redes de conexiones con los investigadores y los practicantes. Con base en una revisión de la literatura correspondiente a los intermediarios de evidencias en la conservación y el manejo ambiental, así como en un cuestionario anónimo que busca a dichas organizaciones, encontramos a pocos intermediarios que cumplieran con estos criterios. Los pocos puentes de evidencias que existen no son capaces de llegar a la mayoría de los practicantes de la conservación, los cuales incluyen a los gestores de recursos en el gobierno y en la industria, a las organizaciones de conservación y a los agricultores y otros terratenientes privados. Argumentamos que la falta de puentes de evidencia entre los investigadores y los practicantes contribuye a la indulgencia de evidencias y limita el uso de evidencias en las acciones de conservación. Sin embargo, varias organizaciones existentes ayudan a reducir la brecha entre la evidencia y la práctica y podrían funcionar como base para la construcción de componentes adicionales para los puentes de evidencia en la conservación. Aunque los puentes de evidencias necesitan experiencia con la investigación y con la síntesis de evidencias, también requieren experiencia con la identificación de y comunicación con la comunidad de practicantes que más necesitan una síntesis clara y concisa de la evidencia. 摘要: 对于生物多样性保护实践应更加注重证据的呼声已越来越高, 我们也同意在保护实践中需要改进证据的使用。然而, 如果不能获取更好的证据, 也将无从实现基于证据的保护。与保护领域不同的是, 在医学领域中, 由已确立并资金充足的中介人或中介组织与医务人员合作, 来整合与决策相关的第一手研究资料, 从而使这些研究证据更易于获取。这些中介机构会准备有针对性的证据摘要, 并将其分发给需要进行较强时效性、主观性决策的医务人员。为了提高效率, 中介机构 (我们称之为"证据桥梁") 应根据医务人员的优先排序来确定研究课题、整合证据、准备和分发易获得且易使用的证据摘要, 并发展和保持研究者与医务工作者的联系网络。基于对保护及环境管理领域证据中介研究的文献调研, 以及此类机构的匿名问卷搜索, 我们发现很少有中介能达到全部标准。现有的少量证据桥梁无法影响到大多数包括政府和行业的资源管理人员、保护组织、农民及其他私人土地所有者在内的保护实践者。我们认为, 缺乏从研究到实践者的证据桥梁会导致"证据自满", 并限制保护行动中的证据使用。尽管如此, 已有的一些组织能帮助缩小证据与实践之间的差距, 并可作为建立保护证据桥梁额外组成部分的基础。建立证据桥梁不仅要有研究和证据整合的专门知识, 还要有识别出最需要清晰简明的整合证据的实践者群体并与之沟通的专门知识。 【翻译: 胡怡思; 审校: 聂永刚】